State of the Heart : South Carolina Writers on the Places They Love - Rogers, Aïda (Book collections on Project MUSE., 2013)
This book is an artful love letter to South Carolina, with contributions from a host of nationally and regionally recognized writers who've written short essays on the places that they cherish. This anthology provides a multifaceted historical and personal view of the Palmetto State. Thematically organized, this collection offers a geographic and emotional scope that is as diverse as its contributors. Sportswriters describe beloved arenas; historians reflect on church ruins and forts. A playwright recalls the magic of her first theater experience; a food writer revels in a coastal joint that serves fresh oysters. Backyards, front porches, a small library at a children's home, the drama and camaraderie of building the Savannah River Site, and places that are gone except in the memories of the writers who loved them - these are just a few of the locales covered, all showing how South Carolina has changed and inspired people in a variety of ways. This book evokes a sense of history and timelessness by bringing together heartfelt responses to South Carolina locales rooted in memory, drawing on reflection, inspiration, and love. The anthology reveals a state that is more than a playground for tourists; it's a state of human hiding places that echo in the hearts of its literary citizens. Though presented as a book about place, the collection is ultimately about our shared connections to one another, to a complex common past, and to ongoing efforts to frame and build a future of promise and possibility. --